The impact of the ban on elective surgery in New York City during the coronavirus outbreak on gynecologic oncology patient care - Sarah S. Lee; Danial Ceasar; Benjamin Margolis; Pooja Venkatesh; Kevin Espino; Deanna Gerber; Leslie R. Boyd (Elsevier, 2022)
Introduction: Elective surgical procedures were suspended during the coronavirus disease pandemic (COVID-19) in New York City (NYC) between March 16 and June 15, 2020. This study characterizes the impact of the ban on surgical delays for patients scheduled for surgery during this first wave of the COVID-19 outbreak. Methods: Patients who were scheduled for surgical treatment of malignant or pre-invasive disease by gynecologic oncologists at three NYC hospitals during NYC's ban on elective surgery were included. Outcomes of interest were the percentage of patients experiencing surgical delay and the nature of delays. Kruskal-Wallis, chi-square, and logistic regression tests were performed with significance set at p < 0.05. Results: Of the 145 patients with malignant or pre-invasive diseases scheduled for surgery during the ban on elective surgery, 40% of patients experienced one or more surgical delays, 10% experienced two or more and 1% experienced three surgical delays. Of patients experiencing an initial delay, 77% were hospital-initiated and 11% were due to known or suspected personal COVID-19. Overall, 81% of patients completed their planned treatment, and 93% of patients underwent their initially planned surgery. Among patients for whom adjuvant therapy was recommended, 67% completed their planned treatment, and the most common reasons for not completing treatment were medically indicated followed by concerns regarding COVID-19. Conclusion: During the ban on elective surgery in NYC during the first outbreak of the COVID-19 pandemic, many patients experienced minor surgical delays, but most patients obtained appropriate, timely care with either surgery or alternative treatment.